Validation of a three-dimensional model about sleep: habits, personal factors and environmental factors - Rebelo-Pinto, Teresa (2016)
Objectives: The present study aims to test the factor structure of two sleep questionnaires and their internal consistency in a sample of adolescents and their respective parents and to evaluate the validity and robustness of a three-dimensional model about sleep, addressing nine subcategories related to sleep habits, personal and environmental factors. Methods: Participants were 654 adolescents from Portuguese schools, who completed “My Sleep and I” questionnaire, and 664 parents who completed “My child׳s sleep” questionnaire; to them confirmatory factor analysis was applied. Results: Confirmatory factor analysis indicate that a nine-factor model has better fit indices compared with the others tested models for both samples (adolescents: χ2/df (Chi-square/degrees of freedom)=2.59, Comparative Fit Index (CFI)=.82, Goodness-of-Fit Index (GFI)=.92, Root Mean Square Error of Approximation (RMSEA)=.049, Expected Cross-Validation Index (ECVI)=1.416; Parents: χ2/df=2.89, CFI=.85, GFI=.91, RMSEA=.053, ECVI=1.528). Moreover, the comparison of the models through Δχ2 index (chi-square difference between rival models) indicates a better fit for this model, Δχ2 (24)=186.5, p<.001 for adolescents and Δχ2 (24)=209, p<.001 for parents. Also, the three second-order factors have good internal consistency, convergent and discriminant validity for all factors in both samples. Conclusions: Results postulate that the three factors and their nine subcategories account for correlations between sleep habits, self-perceptions and knowledge about sleep.